Base of thumb osteoarthritis in UK interface services—a cohort and survey-based study to assess current practice. (28th December 2020) - Dean, Benjamin J F; Kluzek, Stefan; Carr, Andrew J; Hopewell, Sally; Richards, Duncan; Riley, Nicholas; Cuff, Andrew; ,
Abstract: Objective: Base of thumb OA (BTOA) is a common age-related disease that has a significant negative impact on quality of life, while little is known about the structure and pathways of interface services. Our aim was to assess disease burden, referral pathways, service structure and management pathways in UK interface services. Methods: A structured questionnaire was carried out with a participating clinician at each centre to detail the local guidelines and management of BTOA. Five patients referred with BTOA were prospectively identified in each of 32 UK interface centres. Results: Most centres (72%) had a local guideline and a standardized treatment regime consisting of education (100%), joint protection (100%), range of motion exercises (84%), strengthening exercises (88%), splintage (100%) and use of assistive devices (78%). No centre routinely offered a steroid injection at the first appointment and no centre had a specific threshold for offering an injection. Injection delivery was variable. Most patients had not been referred previously (82%). Most patients used analgesia (72%), but a minority of patients had been treated with a splint (46%), therapy (43%) and steroid injection (27%) prior to their latest attendance. Conclusion: Most BTOA patients newly referred to interface services have been treated with analgesics and have not received comprehensive multimodal intervention. The management of BTOA at interface services is standardized in terms of education, splintage and therapy. However, there is a lack of standardization in terms of both the threshold for, timing of and mode of delivery of injection therapy.